Geodynamic context for the deposition of coarse‐grained deep‐water axial channel systems in the Patagonian Andes. (24th May 2014) - Ghiglione, M. C.; Likerman, J.; Barberón, V.; Beatriz Giambiagi, L.; Aguirre‐Urreta, B.; Suarez, F.
Abstract We present field and seismic evidence for the existence of Coniacian–Campanian syntectonic angular unconformities within basal foreland basin sequences of the Austral or Magallanes Basin, with implications for the understanding of deformation and sedimentation in the southern Patagonian Andes. The studied sequences belong to the mainly turbiditic Upper Cretaceous Cerro Toro Formation that includes a world‐class example of conglomerate‐filled deep‐water channel bodies deposited in an axial foredeep depocentre. We present multiple evidence of syntectonic deposition showing that the present internal domain of the fold‐thrust belt was an active Coniacian–Campanian wedge‐top depozone where deposition of turbidites and conglomerate channels of Cerro Toro took place. Cretaceous synsedimentary deformation was dominated by positive inversion of Jurassic extensional structures that produced elongated axial submarine trenches separated by structural highs controlling the development and distribution of axial channels. The position of Coniacian‐Campanian unconformities indicates a ca. 50–80 km advance of the orogenic front throughout the internal domain, implying that Late Cretaceous deformation was more significant in terms of widening the orogenic wedge than all subsequent Andean deformation stages. This south Patagonian orogenic event can be related to compressional stresses generated by the combination of both the collision of the western margin of Rocas Verdes Basin during its closure, and Atlantic ridge push forces due to its accelerated opening, during a global‐scale plate reorganization event.